Identification of TRPV1-Inhibitory Peptides from Takifugu fasciatus Skin Hydrolysate and Their Skin-Soothing Mechanisms - Tang, Haiyan; Chen, Bei; Zhang, Dong; Wu, Ruowen; Qiao, Kun; Chen, Kang; Su, Yongchang; Cai, Shuilin; Xu, Min; Liu, Shuji; Liu, Zhiyu (Marine drugs, 2025)
Skin sensitivity is increasingly prevalent, necessitating new therapeutic agents. This study screened multifunctional peptides from Takifugu fasciatus skin for transient receptor potential vanilloid 1 (TRPV1)-inhibitory and anti-inflammatory activities and investigated their mechanisms in alleviating sensitive skin (SS). A low-molecular-weight hydrolysate was prepared through enzymatic hydrolysis of T. fasciatus skin, followed by ultrafiltration, with subsequent peptide identification performed using nano-HPLC-MS/MS and molecular docking-based virtual screening. Among 20 TRPV1-antagonistic peptides (TFTIPs), QFF (T10), LDIF (T14), and FFR (T18) exhibited potent anti-inflammatory effects in (lipopolysaccharide) LPS-induced RAW 264.7 macrophages. T14 showed the strongest TRPV1 inhibition; T14 (200 μM) inhibited Ca2⁺ in capsaicin-stimulated HaCaT cells by 73.1% and showed stable binding in molecular docking, warranting further analysis. Mechanistic studies revealed that T14 suppressed NF-κB signaling by downregulating p65 protein expression, thereby reducing pro-inflammatory cytokine secretion (G-CSF, GM-CSF, ICAM-1, IL-6, TNF-α) in RAW 264.7 cells. Additionally, T14 (400 μM) inhibited ET-1 in LPS-stimulated endothelial cells by 75.0%; ICAM-1 reached 49.0%. Network pharmacology predicted STAT3, MAPK3, SPHK1, and CTSB as key targets mediating T14’s effects. These study findings suggest that T14 may be a promising candidate for skincare applications targeting SS.